Fi Ra Wali: Revitalisasi Folklor â€œSaguku Hidupkuâ€ Sebagai Identitas Kultural dalam Kosmologi Masyarakat Sentani-Papua - Ruhulessin, Cleopatriza Thonia (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This article aims to describe and explain how the philosophy of fi ra wali (in English:Â my sagoÂ my life)Â shapesÂ the identity of Sentani people. TheÂ objectiveÂ is to explain this notion (fi ra wali)Â features as the cultural identity of the Sentani peopleÂ whichconstructed in everyday engagement (daily interactions) of the SentaniÂ communities.Â Data for the study wasÂ obtained throughÂ Â ethnographic research and phenomenology techniquesÂ includingÂ participant observation, interviews and literature study. Identity is usually constructed institutionally based on juridical and normative agreements collectively.Â This article reveals that identity can be constructed narratively, in daily interactions in society. Everyday angagement (daily life) gives birth to authentic experiences that are sacred in social relations, both in physical space and spiritual space of the Sentani people. IdentityÂ shapedfrom cosmic-cultural reality that exists in cosmology, is able to integrate society in sui generis (clans), in order to face modernization, which has caused social changes in Sentani society.Â This article concludes that the fi ra wali as a cultural identityÂ has importantÂ contributionÂ toÂ deal with multicultural contexts.